Targeting myeloid derived suppressor cells with all-trans retinoic acid is highly time-dependent in therapeutic tumor vaccination. (3rd August 2017) - Heine, Annkristin; Flores, Chrystel; Gevensleben, Heidrun; Diehl, Linda; Heikenwalder, Mathias; Ringelhan, Marc; Janssen, Klaus-Peter; Nitsche, Ulrich; Garbi, Natalio; Brossart, Peter; Knolle, Percy A.; Kurts, Christian; et al.
ABSTRACT: Tumor immune escape is a critical problem which frequently accounts for the failure of therapeutic tumor vaccines. Among the most potent suppressors of tumor immunity are myeloid derived suppressor cells (MDSCs). MDSCs can be targeted by all-trans-retinoic-acid (atRA), which reduced their numbers and increased response rates in several vaccination studies. However, not much is known about the optimal administration interval between atRA and the vaccine as well as about its mode of action. Here we demonstrate in 2 different murine tumor models that mice unresponsive to a therapeutic vaccine harbored higher MDSC numbers than did responders. Application of atRA overcame MDSC-mediated immunosuppression and restored tumor control. Importantly, atRA was protective only when administered 3 d after vaccination (delayed treatment), whereas simultaneous administration even decreased the anti-tumor immune response and reduced survival. When analyzing the underlying mechanisms, we found that delayed, but not simultaneous atRA treatment with vaccination abrogated the suppressive capacity in monocytic MDSCs and instead caused them to upregulate MHC-class-II. Consistently, MDSCs from patients with colorectal carcinoma also failed to upregulate HLA-DR after ex vivo treatment with TLR-ligation. Overall, we demonstrate that atRA can convert non-responders to responders to vaccination by suppressing MDSCs function and not only by reducing their number. Moreover, we identify a novel, strictly time-dependent mode of action of atRA to be considered during immunotherapeutic protocols in the future.